2011
DOI: 10.1097/jnn.0b013e3182135adf
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes Before and After Implementation of a Water Protocol for Patients With Cerebrovascular Accident and Dysphagia

Abstract: The aim of this study was to investigate the impact of a water protocol on the incidence of aspiration pneumonia in persons with cerebrovascular accident and dysphagia admitted to an acute neurologic rehabilitation setting. Retrospective chart review and cohort matching of persons with dysphagia admitted before and after the implementation of a water protocol were carried out. The incidence of aspiration pneumonia was higher in the cohort control group-those patients admitted during the years before the implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 39 publications
0
7
0
2
Order By: Relevance
“…Issues also arise in non-terminally ill patients, for instance where individuals or families decide not to follow recommendations. [97][98][99]169 Careful charting and outcome measurement in such instances helps to further the evidence base around decision making and management. Guideline documents and discussions are available around palliative care and people with dementia.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Issues also arise in non-terminally ill patients, for instance where individuals or families decide not to follow recommendations. [97][98][99]169 Careful charting and outcome measurement in such instances helps to further the evidence base around decision making and management. Guideline documents and discussions are available around palliative care and people with dementia.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Free water protocols (FWP) have come into clinical use in an attempt to address some of the detrimental effects of thin fluid restrictions noted above (decreased quality of life, dehydration, and decreased compliance) while still maintaining the safety afforded by the provision of thickened fluids. Although specific details may vary, like the Frazier Free Water Protocol discussed by Panther [6], these protocols allow patients with documented aspiration to consume thin water under specific conditions [19].…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with previous research on the FWP in the rehabilitation setting. 1,[20][21][22][23][24][25] Participants in the experimental group showed a trend toward decreased days to discharge from the study, but the small number of participants that were followed precluded statistical testing.…”
Section: Discussionmentioning
confidence: 99%
“…19 To date, 7 studies of the FWP in the rehabilitation setting have been published. 1,[20][21][22][23][24][25] Of these, 6 did not reveal elevated rates of aspiration pneumonia in participants on free water protocols. One study, however, showed lung complications, including aspiration pneumonia, in 6 of 42 participants (14%) randomized to a group with access to water but no lung changes in the control group (n = 34).…”
mentioning
confidence: 99%